2020
DOI: 10.1039/d0dt01411g
|View full text |Cite
|
Sign up to set email alerts
|

Highly cytotoxic gold(i)-phosphane dithiocarbamate complexes trigger an ER stress-dependent immune response in ovarian cancer cells

Abstract: Highly cytotoxic AuI-dithiocarbamate complexes were designed to induce severe integrative stress in ovarian cancer cells, leading to the surface exposure of calreticulin, which is a first step in the activation of immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…1,15,16,20 These studies stimulated the development of a wide variety of the linear gold(I)-phosphane complexes that display significant antiproliferative effects. 4,[7][8][9][10][21][22][23][24][25][26][27][28][29][30][31][32][33] Along with the linear gold(I) compounds, the tetrahedral chelated gold(I)-diphosphane cationic complexes have also been recognized as effective cytotoxic agents. 2,3,34,35 It has been demonstrated that the increased lipophilicity of the complexes significantly enhances their cellular accumulation, bioavailability and hence their antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…1,15,16,20 These studies stimulated the development of a wide variety of the linear gold(I)-phosphane complexes that display significant antiproliferative effects. 4,[7][8][9][10][21][22][23][24][25][26][27][28][29][30][31][32][33] Along with the linear gold(I) compounds, the tetrahedral chelated gold(I)-diphosphane cationic complexes have also been recognized as effective cytotoxic agents. 2,3,34,35 It has been demonstrated that the increased lipophilicity of the complexes significantly enhances their cellular accumulation, bioavailability and hence their antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the results obtained in the caspase-3 assay and in the determination of ROS production indicate that gold complexes could have antitumor behavior, being able to induce apoptotic cell death through the increase of ROS levels. The redox potentials of 1 and 2 are outside the biologically accessible redox potential window of −0.4 to +0.8 V, suggesting that these complexes do not directly generate ROS due to the Au(I)/Au(III) process but rather as a consequence of inhibition of TrxR [48]. This inhibition damages the thioredoxin system, an important cellular antioxidant defense, increasing ROS levels, and leading to cell death [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ROS causes mitochondrial membrane depolarization, which produces a disruption of the electron transport chain, leading to the release of cytochrome c and the apoptosis-inducing factor (AIF) from the mitochondria. Cytochrome c release induces caspase-dependent apoptosis, mediated by caspase-3 and caspase-9 activation, whilst AIF is translocated to the nucleus and produces caspase-independent apoptosis [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations